Copyright in historical perspective: from the Middle Ages to the recognition of author's personality rights (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The article discusses the most relevant historical aspects of the copyright. The investigations begin in the Middle and Modern Ages, taking care of the invention of printing, the regime of privileges, as well as the censorship system created by the states to control the literacy works. The paper makes a study about the end of privileges in England and the emergence of the copyright system in 1710, with the entry into force of the Statute of Queen Anne. It examines the literary, artistic and scientific property, which emerged in France with the revolutionary laws of the years 1791 and 1793. Finally, it investigates the construction of the moral rights of the author by the French courts.
Keywords: copyright; rights of personality; intellectual rights; moral rights; privileges system; Statute or Queen Anne; common law; censorship; right of paternity; right to publish; right of integrity; literary artistic and scientific property